Analysis of Changes in Spectral Signal According to Gas Flow Rate in Laser-Induced Breakdown Spectroscopy - Sangwoo Yoon; Hae-Woon Choi; Joohan Kim (Applied Sciences, 2021)
In a laser-induced breakdown spectroscopy (LIBS) system that performs elemental analysis of a target by acquiring the emission of plasma generated on the material surface by a focused laser, the plasma signal may be affected by the flow of the surrounding gas. A flow of gas may be present when LIBS measurements are performed in a special environment where an inert gas is normally applied. In such an environment, the flow of gas may affect the intensity of emission generated in plasma. The LIBS spectral intensity in the gas flow field changes according to the direction of the gas flow and the signal detector of the LIBS. In this case, the correlation between the flow rate and intensity of the spectral line can be confirmed both theoretically and experimentally. In this study, changes in the signal according to the flow rate were theoretically evaluated using the view factor and wave equation. In addition, LIBS signals were examined based on the flow of Ar, N2, and He gases in the experiment. The experimental results confirmed the range of effective gas flow rates over which the correlation between the flow rate and intensity of the LIBS spectral line could be inferred. These results could be used for calibration to achieve accurate measurement of LIBS signals in gas flow fields. In addition, this analysis has the potential to shed light on the properties of flowing gases that affect plasma by reversibly tracking changes in the signal of LIBS in a confined environment.